Architectural regionalism during the neo-classical era: classifying the architectural “Hybrid” stylistic forms - Raja Abdul Kadir, Tengku Anis Qarihah; Mohd Nawawi, Norwina (Universitas Indraprasta PGRI, 2021)
Stylistic architectural changes that occurred during the Colonial era in South East Asian nations such as Malaysia and Indonesia, particularly in the 1800s, had always been simplistically ‘lumped’ together as the Colonial style. Using case studies of the Malay world, this paper argues for the contrasting streams of public architecture, the modernized Malay Classical style; vs the Malayalised Colonial style, though they depict similar combinations of hybrid architectural tectonic language in buildings. This paper argues that various present writings and discourses had ‘hijacked’ the essentially evolving Malay style and had grouped these with the changes attributed to Colonial stylisations, rather than attributing them to the modernization of their own vernacular style. Using aristocratic buildings, the paper highlights cases with the aim to expand the discourse to include the evolving language of local Classical (Malay) architecture, which represent an evolvement from tradition to the Neo-Classical era of modernity. The missing discourse is characteristic of nations undergoing postColonialism attributing to the rupture of history. These essentially regionalized forms within the Neo-Classical era are often mistaken as Colonial pastiche-like borrowings or ‘kitsch’ rather than associated with a broad local early modern vernacular which arises from local phenomena' desire to modernize.